Persistent, arteriopathic ulcers in metameric hemangioma of the lower limb. - Mazzotta, F.; Colonna, V.; Troccoli, T.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
Here are reported three cases of ulcers on hemangioma characterized by 1- occurrence on metameric hemangioma affecting a large area of the lower limb, that is present at birth as telangiectatic precursor, 2- gangrenous appearance of ulcers with well defined borders of arteriopathic type, 3- onset of the ulcerous lesions after the sixth months at the end of the proliferative phase and persistence or recurrence of the ulcers for many months. It is hypothesized that both ulcers and hemangioma are related to the reduced artery flow with consequent tissue hypoxia.